Straightforward and Highly Efficient Synthesis of α-Acetoxy Ketones through Gold-Catalyzed Intermolecular Oxidation of Terminal Alkynes - Wu, Chao; Liang, Zhiwu; Yan, Dong; He, Weimin; Xiang, Jiannan (Synthesis, 2013)
A variety of terminal alkynes were efficiently converted into the corresponding α-acetoxy ketones through gold-catalyzed intermolecular oxidation in the presence of 8-methylquinoline 1-oxide as the oxidant. The reaction probably proceeds through an α-oxo gold carbene intermolecular O–H insertion.
Keywords: alkynes; homogeneous catalysis; gold; oxidations; carbene complexes; ketones; esters